Pengaruh Dampak Era Digital, Budaya Organisasi, dan Keterlibatan Karyawan terhadap Efisiensi Kerja Karyawan pada Perusahaan PT Indogadai Prima di Cabang Kota Tangerang - Widya Setya Ningrum; Syaiful Anwar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine whether there is an influence on the Impact of the Digital Era (X1), Organizational Culture (X2), and Employee Involvement (X3) on Employee Work Efficiency (Y) at PT Indogadai Prima Tangerang City Branch. The research used in this study is quantitative, with a non-probability sampling technique. The sample consisted of 100 respondents representing different job positions, ranging from area managers, store heads, cashiers, to sales clerks. Data were collected through a structured questionnaire using a Likert scale. Furthermore, the data analysis applied descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, and the coefficient of determination using SPSS version 25. The results of this study indicate that the Impact of the Digital Era has a positive but not significant effect on Employee Work Efficiency, Organizational Culture has a significant effect on Employee Work Efficiency, while Employee Involvement does not significantly influence Employee Work Efficiency. Among the independent variables, Organizational Culture is the most influential factor in determining employee efficiency. The findings highlight the importance of strengthening organizational culture to enhance efficiency while ensuring that digital transformation is implemented with strategies that reduce resistance and increase adaptability. This research contributes theoretically to the study of human resource management in the digital transformation era and provides practical recommendations for companies in developing policies to optimize employee efficiency.